1989
DOI: 10.1128/jcm.27.7.1582-1587.1989
|View full text |Cite
|
Sign up to set email alerts
|

Development of a diagnostic test for Johne's disease using a DNA hybridization probe

Abstract: A DNA probe, M13 mpHAW71, that detects Mycobacterium paratuberculosis in the fecal material of infected animals was developed for use in the diagnosis of Johne's disease. The probe detected as few as IO' M. paratuberculosis when hybridized under stringent conditions to total genomic DNA purified from bovine fecal material. When the probe was used diagnostically, it did not differentiate members of the Mycobacterium avium-M. intracellulare-M. paratuberculosis complex. Compared with culturing, the DNA probe iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Earlier attempts to detect M a paratuberculosis directly in faecal samples by PCR have had limited success, limited application or were not reproducible. [17][18][19][20] Although most of and decrease milk production. 1 Aborted bovine foetuses show nonspecific lesions and various degrees of autolysis.…”
Section: Ims-pcrmentioning
confidence: 99%
“…Earlier attempts to detect M a paratuberculosis directly in faecal samples by PCR have had limited success, limited application or were not reproducible. [17][18][19][20] Although most of and decrease milk production. 1 Aborted bovine foetuses show nonspecific lesions and various degrees of autolysis.…”
Section: Ims-pcrmentioning
confidence: 99%
“…All members of the MAC are genetically similar, although the small distinctions between Mycobacterium avium and Mycobacterium intracellulare have been well established (Boddinghaus et al 1990;De Smet et al 1996;Feizabadi et al 1997;Thorel et al 2001). In particular, DNA-DNA hybridization studies have long ago showed significant genetic similarity between MAP and MAA (Saxegaard et al 1988; Yoshimura and Graham 1988;Hurley et al 1989). More recently, a >98% nucleotide identity was shown to exist when comparing MAP and MAA genomes with each other .…”
Section: Introductionmentioning
confidence: 99%
“…Several DNA probes for the detection of MAP have been described. 13,19,21 More recently, several polymerase chain reaction (PCR) tests to detect MAP DNA have been developed. 1,5,8,23,27,29 The purpose of this study was to compare 3 PCR-based diagnostic kits with a conventional culture method for the detection of MAP in bovine fecal samples.…”
Section: Introductionmentioning
confidence: 99%